2021
DOI: 10.1111/cas.15180
|View full text |Cite
|
Sign up to set email alerts
|

Predictive model for recurrence of renal cell carcinoma by comparing pre‐ and postoperative urinary metabolite concentrations

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Ratios may be considered as an internal normalization of confounders such as different diets and life styles among patients and may contribute to reduce the systematic experimental error . Models based on different combinations of plasma lipid ratios were suggested as potential biomarkers for the diagnosis and prognosis of endometrial cancer, and ratios of urine estrogen levels were suggested for breast cancer risk evaluation. , Regarding ccRCC, the ratio between urine metabolite concentrations in pre- and post-surgery (3–7 days) samples were suggested as potential biomarkers for recurrence prediction based on multiple logistic regression analysis . Although in our lipid profiling study the linear response of the detected ionic species for PC 16:0/0:0, PC 18:2/18:2, and linoleic acid was not evaluated, our results highlight that the ratio between PC 16:0/0:0 and PC 18:2/18:2 with linoleic acid may be a useful marker for patient prognosis.…”
Section: Resultsmentioning
confidence: 94%
“…Ratios may be considered as an internal normalization of confounders such as different diets and life styles among patients and may contribute to reduce the systematic experimental error . Models based on different combinations of plasma lipid ratios were suggested as potential biomarkers for the diagnosis and prognosis of endometrial cancer, and ratios of urine estrogen levels were suggested for breast cancer risk evaluation. , Regarding ccRCC, the ratio between urine metabolite concentrations in pre- and post-surgery (3–7 days) samples were suggested as potential biomarkers for recurrence prediction based on multiple logistic regression analysis . Although in our lipid profiling study the linear response of the detected ionic species for PC 16:0/0:0, PC 18:2/18:2, and linoleic acid was not evaluated, our results highlight that the ratio between PC 16:0/0:0 and PC 18:2/18:2 with linoleic acid may be a useful marker for patient prognosis.…”
Section: Resultsmentioning
confidence: 94%
“…Additionally, poor prognosis, and resistance to second-line treatment are associated with urinary glutamate levels. In our previous research, the accurate quantification of urinary glutamate reflected the malignant and recurrent status of RCC after definitive therapy [ 16 , 17 ]. Elevated glutamate levels have also been reported to be associated with poor prognosis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the detection of changes in circulating metabolite profiles can reveal cancer-induced abnormalities in biometabolic pathways and associated biological behaviors, thus effectively differentiating Patients with RCC from healthy populations, distinguishing ccRCC from other subtypes of RCC, and evaluating treatment efficiency and prognosis. Currently, the analysis of metabolites mainly depends on mass spectrometer (MS)-based methods, including liquid chromatography-MS (LC–MS), gas chromatography-MS (GC–MS), matrix-assisted laser desorption/ionization-MS (MALDI), and related derivative techniques such as ultra-performance LC–MS (UPLC-MS) or headspace solid-phase microextraction coupled with GC–MS (HS–SPME–GC–MS) [ 100 104 ]. By accurately measuring compound masses and inferring chemical composition and structure, MS has shown high sensitivity and specificity for probing compounds, becoming the preferred method for structural identification of analytes in complex mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to MS, NMR has lower sensitivity and specificity but can provide more detailed structural information. However, metabolite profiles vary widely among individuals, and although some compounds, such as 2-hydroxyglutarate (2HG), have been co-detected in several clinical trials [ 100 , 106 ], the panel of compounds used in most experiments is inconsistent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation